(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Starting from the personal experience of advanced care planning (PCC) of one of the authors, a person affected by spinal muscular atrophy, the authors provide ethical, clinical, and legal considerations regarding the actual implementation of PCC in the context of rare diseases. The focus is on both the perspective of the patient requiring care and that of the clinician providing care, with particular attention to the ongoing relational process between the parties. The contribution also analyzes the PCC model proposed to the author and the need for greater public and institutional communication on the subject.